URBAN RESTRUCTURING AND SOCIO-SPACE SEGREGATION - Novaes, Camila Pontin [UNESP]; Bernardes, Adilson Toledo [UNESP] (Univ Federal Ceara, Programa Pos-graduacao & Filosofia, 2015)
The implementation of urban projects related to mega sports events held in Brazil, and hegemonic interests, outweigh the popular interests related to the right to housing. Following the market logic of capital accumulation needs outweigh the importance of belonging of the individual or the group as a social context for the post concerned, displacing individuals without worrying about the consequences to the daily life of the same. The restructuring of space encompasses the production spaces, spaces of consumption and circulation, as well as the reproduction of spaces. There is, therefore, a relationship between the productive restructuring, started from the crisis of Fordism, and the restructuring that operates in intraurbans and intercity spaces. From the segregation that dynamic capitalist notions of (ex) appropriation of urban space and its latent commercialization, there is in this Brazilian urban setting, especially in slum areas, a tendency to Urban Restructuring.
Keywords: urban restructuring; socio-spatial segregation; urban space